2020
DOI: 10.1186/s13063-020-4079-8
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining and cycle time reduction of the startup phase of clinical trials

Abstract: Objective: The startup phase of a clinical trial (CT) plays a vital role in the execution of new drug development. Hence, the aim of this study is to identify the factors responsible for delaying the CT startup phase. Further, it focuses on streamlining and reducing the cycle time of the startup phase of newly sponsored CTs. Methods: Thirteen sponsored CTs conducted between 2016 and 2017 at the Clinical Research Department of King Fahad Medical City, Riyadh, Saudi Arabia, were considered for this study. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Krafcik et al described a 319-day median start-up time in a review of 38 heterogenous studies ranging from 2004 to 2016 in Boston, Massachusetts. Similarly, a 174-day start-up time across 13 Saudi clinical trials was reported by Abu-Shaheen et al, with a significant portion of that time dedicated to obtaining local IRB approval. To limit loss of resources spent on the contractual process without regulatory approval and vice versa, many institutions complete the regulatory approval process and contract negotiations consecutively rather than concurrently.…”
Section: Discussionmentioning
confidence: 74%
“…Krafcik et al described a 319-day median start-up time in a review of 38 heterogenous studies ranging from 2004 to 2016 in Boston, Massachusetts. Similarly, a 174-day start-up time across 13 Saudi clinical trials was reported by Abu-Shaheen et al, with a significant portion of that time dedicated to obtaining local IRB approval. To limit loss of resources spent on the contractual process without regulatory approval and vice versa, many institutions complete the regulatory approval process and contract negotiations consecutively rather than concurrently.…”
Section: Discussionmentioning
confidence: 74%
“…Delays in study start-up and the inability of clinical research studies to meet their targeted enrollment metrics can negatively affect the validity of study results, reduce their generalizability to the broader population by impacting study completion timelines, and subsequently influence the quality of trials for these reasons [ [24] , [25] , [26] , [27] , [28] , [29] ]. The literature surrounding the use of trial facilitators to guide assigned study sites through clinical trial start-up and enrollment phases is limited, and the use of facilitators in research settings is exclusively related to clinical care positions and/or teams that either primarily focus on developing research capacity and building research culture within organizations, or supporting the implementation of findings from trials into medical practices using unique, tailored intervention strategies [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Streamlining the launch phase will result in a shorter mean trial phase and faster IRB approval, resulting in better recruitment of subjects in the future through better activation phase planning and execution. 26 Integrating several subtrials to maximize accrual numbers and minimize logistical hassles is a one-of-a-kind way for master protocols to expedite the development of therapies and decrease futility. 27 Among the 21 trials registered on Clinicaltrials.gov, only 5 produced publications retrievable on PubMed and referenced by the NTCID.…”
Section: Trial Duration and Lack Of Published Researchmentioning
confidence: 99%